2019
DOI: 10.1371/journal.pone.0211933
|View full text |Cite
|
Sign up to set email alerts
|

The moderating role of sportsmanship and violent attitudes on social and personal responsibility in adolescents. A clustering-classification approach

Abstract: The aim of this study was to classify a randomized sample of adolescents according to their violent and sportsmanship attitudes to determine the influence of personal and social responsibility levels on each cluster. The sample comprised of 595 adolescents, aged between 12 and 15 years old (M ± SD = 13.9 ± 2.3 yr). Participants completed the Multidimensional Orientations Towards Sports Scale, the California School Climate and Safety Survey and the Personal and Social Responsibility Questionnaire. Cluster analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 35 publications
2
16
0
2
Order By: Relevance
“…On the other hand, no improvements were found in the violence perception, despite the fact that former studies in the PE field, such as [55][56][57][58], related higher responsibility and sportsmanship levels with lower violence and disruptive behavior levels. In line with the present work, similar results have been already obtained without changes in the violence perception in the study by Manzano-Sánchez and Valero-Valenzuela [54], where, despite the decrease in antisocial behavior, there was no change in the student violence perception who received the TPSR program.…”
Section: Discussionmentioning
confidence: 78%
“…On the other hand, no improvements were found in the violence perception, despite the fact that former studies in the PE field, such as [55][56][57][58], related higher responsibility and sportsmanship levels with lower violence and disruptive behavior levels. In line with the present work, similar results have been already obtained without changes in the violence perception in the study by Manzano-Sánchez and Valero-Valenzuela [54], where, despite the decrease in antisocial behavior, there was no change in the student violence perception who received the TPSR program.…”
Section: Discussionmentioning
confidence: 78%
“…In this way, the use of pedagogical approaches in the educational context can allow the necessary conditions to be reached to promote responsibility, BPN, and self-determined motivation of students in the classroom [ 32 ], creating a school social climate that favors the development of prosocial behavior among students, while decreasing antisocial and violent behavior. In fact, the study by Courel-Ibáñez et al [ 21 ] concluded that improved development of personal and social responsibility in adolescents will contribute significantly to a reduction in violent behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Courel-Ibañez et al [ 21 ] suggest the establishment of structured programs to promote personal and social responsibility as a trigger for positive behavioral, affective, and emotional consequences. One pedagogical model that attaches “best consequences” with regard to value development is the personal and social responsibility model (TPSR), designed by Donald Hellison [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The practice of sports can lead to the development of values such as respect, self-control, effort, autonomy and leadership [ 1 ]. However, sport can only foster educational habits and values if it is properly timed and specifically focused towards that end [ 2 – 4 ].…”
Section: Introductionmentioning
confidence: 99%